Stabilitas Emulsi Minuman Virgin Coconut Oil dengan Pelarut Air Kelapa - Nur Mu’min; Rizka Oktavia (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2021)
Virgin Coconut Oil (VCO) is a pure coconut oil product whose manufacturing process does not involve the heating process and the workmanship is very simple. VCO is reportedly able to prevent and treat various diseases such as being able to kill viruses, bacteria, increase endurance and moisturize the skin so that people are increasingly interested in consuming it, but its "oily" taste causes VCO products in the form of packaging drinks to be less popular. This study aims to determine the stability of VCO emulsions with the addition of coconut water at variations in concentration. The working procedure carried out is the determination of the ratio of coconut water and VCO, determination of emulsifier concentration, viscosity, pH change and creaming index.This study aims to establish a good description of VCO beverage products and favored by panelists.The research method used is the method (experimental methode) using random group design (RAK).